Pengaruh Kualitas Pelayanan dan Jaminan Keselamatan Terhadap Kepuasan Penumpang di Bandar Udara International Juanda Surabaya - Muhammad Ikhsan; Kifni Yudianto (Journal of Creative Student Research, 2024)
In achieving comfort, security and flight safety, there are several things and requirements that must be considered and fulfilled by airport managers. First, reliable and professional human resources in terms of security, safety and passenger comfort. In this case all airport officers must be able to guarantee the comfort, safety and satisfaction of passengers. This study aims to determine the effect of service quality and safety assurance on passenger satisfaction at Juanda International Airport Surabaya. This research uses quantitative methods. Respondents in this study amounted to 100 passengers at Juanda International Airport Surabaya. Data obtained through offline questionnaire distribution. The data analysis technique uses Multiple Linear Regression Test, T Test, F Test and Coefficient of Determination Test. The results of this study indicate that there is an effect of service quality and safety assurance on passenger satisfaction at Juanda International Airport Surabaya. Evidenced from the results of the T-Test (Partial), it is known that T count is 8.159 and 11.067 with a significance value obtained of 0.01 <0.05, this states that partially the service quality variable has an effect on the passenger satisfaction variable and the results of the F test are known that the results of the f test produce a significance of 0.001 <0.05, which means that service quality and safety assurance have a significant effect on passenger satisfaction. The results of the Coefficient of Determination Test show a result of 58.7% which means that service quality and safety assurance influence passenger satisfaction while the remaining 41.3% is influenced by other factors not examined.